The dying patient: taboo, controversy and missing terms of reference for designers—an architectural perspective. Issue 1 (16th November 2020) - Bellamy, Annie; Clark, Sam; Anstey, Sally
Abstract : Contemporary society has grown seemingly detached from the realities of growing old and subsequently, dying. A consequence, perhaps, of death becoming increasingly overmedicalised, nearly one in two UK nationals die institutional deaths. In this article we, two architectural scholars engaged in teaching, research and practice and a nurse and healthcare scholar with a focus on end-of-life care and peoples' experiences, wish to draw attention to a controversy resulting from a paucity in current literature on the terms of reference of the dying 'patient' as we navigate the future implications of the COVID-19 pandemic. This contributes to a relative lack of touchstones for architects to refer to when designing person-centred palliative care environments. Unlike common building types, architects are extremely unlikely to have lived experience of palliative care environments as patients; and therefore, require the help of healthcare professionals to imagine and empathise with the requirements of a person dying away from home. This paper includes a review of ageing and dying literature to understand, and distil from an architectural perspective, who, design professionals, are designing for and to remember the nuanced characteristics of those we hold a duty of care toward. We ask readers to heed the importance of accurate terms of reference, especially when commissioning and/or designing environments of palliative care. Furthermore, we put forward an appeal for interdisciplinary collaboration to develop a framework for codesigning positive experiences of person-centred care and environments at the end of life.